Analisis Peran Kepuasan Kerja dan Budaya Kerja Terhadap Kinerja Pegawai - Joko Rizkie Widokarti; Eduard Yohannis Tamaela; Milcha Handayani Tammubua (Universitas Yapis Papua, 2023)
This research aims to find out and analyze the magnitude of the effect of causality between organizational culture, job satisfaction and employee performance of Dr. Haulussy Ambon. Based on the research objectives above, this type of research can be classified as an explanatory research (exsplanatory). Through surveys using questionnaire and interview instruments for data collection and probability sampling methods as well as purposive sampling techniques for sample selection, 111 respondents were obtained as research samples. The results by using path analysis indicate that organizational culture has a positive and significant effect on job satisfaction and performance and job satisfaction has a positive and significant effect on the performance of RSUD Dr. Haulussy Ambon. Thus it can be said that the drive to improve organizational culture will increase the level of performance and subsequently the drive to increase job satisfaction will increase the level of employees’s performance of RSUD Dr. Haulussy Ambon